Vaccines for travel and vaccines for adults: moving targets! - McIntosh D. (Клиническая микробиология и антимикробная химиотерапия, 2018)
This short review provides up-to-date information on vaccination problems for travelers and adults in general, including hepatitis B, meningococcal infection, rabies, yellow fever, measles. The article presents the general principles of approaches to vaccination with a focus on those diseases and potential prospects for solving this problem.